Othello Syndrome in Parkinson’s Disease - a review of etiology, diagnosis and management - Bury, Karolina; Koguc, Karolina; Kusibab, Karolina; Bartoszek, Julita (Quality in Sport, 2025)
Introduction: Othello syndrome, also known as delusional jealousy, is a rare subtype of delusional disorder characterized by a persistent, unfounded belief in a partner's infidelity. Although classically associated with psychiatric disorders, OS is increasingly recognized in the context of neurological diseases, particularly Parkinson’s disease. This review explores the epidemiology, pathogenesis, symptomatology, and treatment of OS, with emphasis on its manifestation in PD patients. Materials and Methods: This narrative review examines recent research on OS, focusing on its presentation in PD and current treatment approaches. Sources include studies from 2021-2024 identified via PubMed database, along with DSM-5 and ICD-10 guidelines. Results: The prevalence of OS ranges from 0.5-1.4% in psychiatric populations and up to 15.8% in individuals with major neurocognitive disorders, including PD. In PD, delusional jealousy is the second most common type of delusion after persecutory delusions and is most commonly linked to dopamine agonist therapy rather than PD dementia. Neuroimaging studies suggest dysfunction in the frontal-limbic circuitry, especially in the right prefrontal cortex, contributes to the development of OS. Symptoms include fixed delusions of infidelity, compulsive behaviours, emotional dysregulation, and occasionally, visual hallucinations. These often result in interpersonal conflict, aggression, and increased risk of suicide and homicide. Conclusions: Management of OS in PD is complex and often requires modification of dopaminergic treatment. Reducing or discontinuing dopamine agonists may alleviate symptoms but can exacerbate motor dysfunction. Atypical antipsychotics, mood stabilizers, and SSRIs have shown benefit. Recognition of OS is crucial, as its impact on patient quality of life and interpersonal relationships can be profound. Early diagnosis and individualized treatment are essential to prevent escalation to violence or psychiatric crises.